Diálogo e linguagem : subsídios teóricos de Paulo Freire e Lev Vygotski para a aprendizagem dialógica - Wurzler, Denise (2017)
We present the research of Master in Education developed in the PPGEDU of UFMT - Campus of Rondonópolis with the theme: Dialogue and Language: Theoretical subsidies of Paulo Freire and Lev Vygotski for the dialogical learning". In this dissertation we analyze the articulation between the concepts of Freire's dialogue and the language of Vygotski, understood in the elaboration of Dialogic Learning, as a possible answer to the educational challenges of the Information Society. In order to verify the concepts of dialogue (in Freire) and language (in Vygotsky) that contributed to the construction of the theoretical bases of the Dialogic Learning. We analyze in the works of the two authors the articulation of these concepts of Language in Vygotski and Dialogue in Freire. The methodology used for this research is qualitative bibliographical in nature and we use to analyze the data, the Content Analysis. Therefore, we bring in our research the importance of dialogue and language through social interaction, for the construction of Dialogic Learning. The research aims to contribute to the educational scenario by reflecting on dialogue and language as the center of social interactions in Contemporaneity.